Characteristics of the composition of stingless bee bread with health benefits originating from the Kulisusu Subdistrict, North Buton Regency - Uslinawaty, Zakiah; Pujirahayu, Niken; Rosmarlinasiah, Rosmarlinasiah; Hadjar, Nurhayati; Kabe, Abigael; Hendri, Hendri (Universitas Aisyah Pringsewu, 2023)
This study aims to determine the chemical composition of stingless bee bread from Kulisusu District, Buton Utara Regency. Meanwhile, this research aims to obtain information on the composition of stingless bee bread and the source of nectar, and pollen from Kulisusu District, Buton Utara Regency. The research took place from October to November 2021. Bee Bread samples were taken from beehives in the Forest of Kulisusu District, Buton Utara Regency. Determination of the chemical components of Bee Bread using a spectrophotometer in the Biomedical Laboratory, Faculty of Medicine, Halu Oleo University. The results showed that there were two types of stingless bees, namely Tetragomula sapiens and Tetragomula biroi. 14 types of plants have been identified as food sources for stingless bees. The chemical composition of Bee Bread is the average protein content of T, sapiens is 27.00% and T, biroi is 12%. The average carbohydrate content of T, sapiens is 45.57%, and T, biroi is 58.11%. on the average polyphenol content of T, sapiens is 9.88%, and T, biroi is 22.56%.